Efforts To Improve History Learning Activity And Results Through Quantum Teaching Model With Melody Stick Media - Bramasta Agung Pambudi; Nunuk Suryani; Isawati Isawati (Universitas Sebelas Maret, 2020)
This study aims to improve the activeness and learning outcomes of students through the application of the Quantum Teaching learning model with the Melody Stick media.This research is a Classroom Action Research (CAR). The study was conducted in two cycles consisting. The research subjects were class XI IPS 4 of SMA Negeri 1 Karanganyar, with a total of 36 students. The results showed that: the application of the Quantum Teaching learning model with the Melody Stick media could increase the activeness of students. This is evidenced by the increase in the average achievement indicator of activeness from 60.12% in the pre-cycle, to 70.71% in the first cycle, and 83.27% in the second cycle. the application of the Quantum Teaching learning model with the Melody Stick media can improve the learning outcomes of students. This is evidenced by the increase in the percentage of students completing history learning, namely 41.67% in the pre-cycle, increasing to 63.89% in the first cycle, and 83.33% in the Based on the results of the study it can be concluded that the application of the Quantum Teaching learning model with the Melody Stick media can increase the activeness and learning outcomes